Defect Analysis of 316LSS during the Powder Injection Moulding Process - ., M Rafi Raza, Faiz Ahmad, MA Omar, RM German, Ali S Muhsan (2012)
Austenitic Stainless Steel Has a FCC Structure at Room Temperature and the Temperature Range of the Austenite Phase Depends upon its Composition. 316L SS Is Widely Used in Medical, Marine, Industrial, Sporting and Aerospace Applications due to its Excellent Combination of Mechanical Properties and Corrosion Resistance. this Study Presents the Defects Observed during Optimization of the Processing Parameters for the Fabrication of Powder Injection Molding (PIM) of 316L SS Parts.